2019
DOI: 10.3389/fphar.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

Sishen Wan® Ameliorated Trinitrobenzene-Sulfonic-Acid-Induced Chronic Colitis via NEMO/NLK Signaling Pathway

Abstract: The nuclear factor (NF)-κB signaling pathway plays an important role in the initialization and development phase of inflammatory injuries, including inflammatory bowel disease (IBD). Sishen Wan (SSW) is a classic Chinese patent medicine listed in the Chinese Pharmacopoeia, which is usually used to treat chronic colitis; however, it is unclear whether SSW can treat IBD via the NF-κB signaling pathway. In the present study, the therapeutic effect of SSW was demonstrated by the decreased index of colonic weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The nine major bioactive components of SSP, deoxyschizandrin, γ-schizandrin, schizandrin, schizandrol B, schisantherin A, psoralen, isopsoralen, evodiamine, and rutaecarpine, have been analyzed by high performance liquid chromatography (HPLC) coupled with electrospray tandem mass spectrometry (ESI-MS/MS; Zhang et al, 2018). Our previous studies have shown that SSP attenuates the symptoms of trinitrobenzene-sulfonic-acid induced colitis by restraining nuclear factor-κB activation via inhibiting the NEMO/NLK signaling pathway (Wang et al, 2019), indicating that SSP had certain effect on colitis, but whether it affected the development of ulcerative colitis by another way has not been known. However, it is unknown whether SSP is active against experimental colitis by regulating the balance between inflammatory DCs and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…The nine major bioactive components of SSP, deoxyschizandrin, γ-schizandrin, schizandrin, schizandrol B, schisantherin A, psoralen, isopsoralen, evodiamine, and rutaecarpine, have been analyzed by high performance liquid chromatography (HPLC) coupled with electrospray tandem mass spectrometry (ESI-MS/MS; Zhang et al, 2018). Our previous studies have shown that SSP attenuates the symptoms of trinitrobenzene-sulfonic-acid induced colitis by restraining nuclear factor-κB activation via inhibiting the NEMO/NLK signaling pathway (Wang et al, 2019), indicating that SSP had certain effect on colitis, but whether it affected the development of ulcerative colitis by another way has not been known. However, it is unknown whether SSP is active against experimental colitis by regulating the balance between inflammatory DCs and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Sishen Pill (SSP) is the classic prescription of traditional Chinese medicine (TCM) for 1,000 years, and frequently-used to treat IBD, allergic colitis, chronic colitis, irritable bowel syndrome (IBS), and so on (Wang et al, 2019a). In clinic, SSP is widely accepted by IBD patients for definite therapeutic effect, little adverse reaction, and lower recurrence rate (Lu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…7.81−500 ng/mL for 17 and 20; 1.61−103.13 ng/mL for 4; 1.46−93.75 ng/mL for 7; 1.95−125 ng/mL for 0.98−62.50 ng/mL for the other compounds. For the method validation, the low, middle, and highquality control (QCL, QCM, QCH) samples were prepared by mix appropriate aliquots of 26 stock solutions in MeOH:…”
mentioning
confidence: 93%
“…from Beijing John Long Technology Development (Beijing, China) and Chengdu Push Biotechnology (Chengdu, China), respectively. (-)-Licarin-B (2) [30], isopsoralen (8), psoralen (9), psoralidin (1), lespecyrtin B1 (3), isobavachromene (4), isobavachalcone (5), psorachalcone A (6), bavachin (7), neobavaisoflavone (15) [18,20,21,[31][32][33], 10-methoxywuchuyuamide I (10), dehydroevodiamine (11), wuchuyuamide-I (12), wuchuyuamide-III (14), evodiame (16), rutaecarpine (19), evocarpine (23), 1-methyl-2-decyl-4(1H)-quinolone (26) [34][35][36] were isolated from PC, MF, EF in our laboratory with the purity ≥98% which the structure identification were completed by 1 H-NMR, 13 C-NMR, and TOF-MS spectral analyses as described in our previous reports. Carbamazepine (Internal standard, IS, Cat No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation